#TITLE_ALTERNATIVE# - Widodo NIM. 95004012, Hendro
Abstract : Drainage system in coastal area becomes the important issue to be studied because it has an unique character compare with non-coastal area. Coastal city have important issue due to the more big city in the world located in coastal area. The coastal area to be defined as an area that have 60 kms width from coastal line with 75% population in 2025 and more over 23 big city in the world 16 located on coastal area. It has flat topography, tidal effect in drainage system outlet, and storm water (run oft) can not flow by gravitation. The handling system of drainage have special character like polder, detention, retention and pumping to flow the excess water to recipient water (river, like or lake). The each handling system have advantage and disadvantage. The result of analyze rainfall indicate that storm in coastal city have the rainfall distribution in first and second hours, and rainfall even for 6 hours. The typical rainfall in non-coastal area indicates that rainfall distribution almost spread in 24 hours. With case study in system drainage Medokan basin Surabaya city, the problem is grow up when inundation in level 30 -50 cm in rainy seasons. The problem is executed by modeling HEC - HMS and HEC - RAS, it's indicate that water level over flow from levee with return periods 5 years, in existing condition and design condition. The existing condition with pumping 4 x 0.9 m3/second and the design system with reservoirs 2 ha area and additional pump capacity m3/sec and 2x5 m3/sec. The design condition just reduce inundation, the problem can be solved by canal rehabilitation in upstream Medokan and upstream Semolo.